Bioefficacy, phytotoxicity, safety to natural enemies and residues of flubendiamide in sugarcane (Saccharum spp. L.) under field conditions. (October 2017) - Madhu Sudhanan, E.; Krishnamoorthy, S.V.; Kuttalam, S.
Abstract: Sugarcane early shoot borer, Chilo infuscatellus Snellen is a major menace and cause of considerable damage to sugarcane crops in India. The incidence of early shoot borer has been increasing for the last few years. A new insecticide flubendiamide was evaluated in the field to assess its bioefficacy against sugarcane early shoot borer during February to December 2013 and August 2013 to July 2014. Two rounds of foliar application of flubendiamide 20 WG at 60 and 50 g a.i. ha −1 significantly reduced the early shoot borer in both experiments. Foliar application of flubendiamide 20 WG (50, 100 and 200 g a.i. ha −1 ) in sugarcane did not cause any phytotoxic symptoms. Flubendiamide 20 WG test doses were found to be safe to natural enemies including spiders and coccinellids in the field. Though there was a short term decline in the natural enemy population, it started increasing gradually within a fortnight after treatment. The sugarcane yield increased over the control in the flubendiamide 20 WG (60 g a.i. ha −1 ) treated plots by 32.7 and 31.5% in the two seasons, respectively. The residues of flubendiamide at 50 and 100 g a.i. ha −1 were below detectable levels in sugarcane leaf, juice and soil at harvest. Highlights: Foliar application of flubendiamide 20 WG (60 and 50 g a.i. ha −1 ) significantly reduced the sugarcane early shoot borer damage. Sugarcane yield was increased over control in all the flubendiamide 20 WG treated plots. The treatment reduced the natural enemy population in the field initially and increased gradually at 20 days after treatment. Foliar application of flubendiamide in sugarcane did not cause any phytotoxic symptoms. The residue analysis in sugarcane leaf, juice and soil after harvest revealed that the residues were below at detectable level.